Memaknai Metafora Kerajaan Allah dalam Kehidupan Gereja: Antara Utopia atau Existensi - Simanjuntak, Fredy; Siagian, Fereddy (MAGNUM OPUS: Jurnal Teologi dan Kepemimpinan Kristen, 2021)
The presupposition of God's Kingdom was initially eschatological in relation to the Kingdom of Israel. In the Gospels Jesus often uses the Metaphor of God's Kingdom in conveying His teachings. Jesus often reinterpreted the concept of the kingdom of God formed in the wrong Jewish tradition with hope for its geographical nature. On the contrary in the Church itself, especially the Pentecostal/charismatic school. Interpretations of this topic are often taught partially in certain parts and not as a whole. Not a few seminars are held that discuss the condition of the age to come which is only centered on the second coming of Christ but the discussion of the present is ignored. The emphasis tends to be more eschatological in the future but less responsible for daily life. Jesus' emphasis on the concept of the kingdom of God never replaced the present with a state of being far away in the future. In essence, the picture of the Kingdom of God taught by the Lord Jesus recorded by the Gospel is full of spiritual values and not talking about the visible. This study is a text analysis of Gospel texts to interpret what is said in the Gospel texts regarding the Kingdom of God.